To teach or not teach controversial public issues in Taiwan?. Issue 4 (2nd October 2019) - Hung, Yu-Han
ABSTRACT: This study is aimed at exploring how teachers make curricular-instructional decisions regarding teaching contemporary controversial public issues in Taiwan (e.g., national identity, sovereignty, and ethnic issues). Using a case study design, this study documents how six social studies teachers make curricular decisions about whether to teach controversial public issues or not, and how teachers develop the curriculum and pedagogy for teaching controversial public issues. Findings illuminate that teachers' personal practical knowledge – i.e., their family background and teacher preparation – act as important factors that influence their curricular decision-making. In addition, teachers' curricular-instructional decisions on whether to teach controversial public issues or not reflects an increased autonomy and authority in Taiwan. In sum, this study, refracted through the national context of Taiwan, provides insights into the possibilities that exist within Taiwanese teachers' curricular-instructional decisions and increased autonomy and authority.